2014
DOI: 10.1159/000354326
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mechanical Bowel Preparation before Ileal Urinary Diversion: A Systematic Review and Meta-Analysis

Abstract: Background: Although the use of mechanical bowel preparation (MBP) is still widely promoted as the dogma before patients undergo ileal urinary diversion, an increasing number of clinical trials have suggested that there is no benefit. Thus, we performed a meta-analysis to evaluate the efficacy of MBP in ileal urinary diversion surgery. Methods: A literature search was performed in electronic databases, including PubMed, Embase, Science Citation Index Expanded as well as the Cochrane Library and the Cochrane Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 32 publications
(88 reference statements)
1
2
0
Order By: Relevance
“…Meta-analyses[ 8 - 12 ] have been published on MBP in elective colorectal surgery showing mixed results, with most studies demonstrating no difference in infective complications between patients receiving MBP or control treatment, although control treatment varied significantly between the use of a rectal enema or absolutely no preparation. Similar results have been found in gynaecological[ 13 , 14 ] and urological[ 15 , 16 ] surgery where studies have shown no benefits in visualisation, bowel handling or complication rates between patients treated with bowel preparation and those given no bowel preparation. As a result of this inconclusive evidence, several studies have established that practice varies significantly between countries, and even surgeons in the same institution[ 17 , 18 ].…”
Section: Introductionsupporting
confidence: 82%
“…Meta-analyses[ 8 - 12 ] have been published on MBP in elective colorectal surgery showing mixed results, with most studies demonstrating no difference in infective complications between patients receiving MBP or control treatment, although control treatment varied significantly between the use of a rectal enema or absolutely no preparation. Similar results have been found in gynaecological[ 13 , 14 ] and urological[ 15 , 16 ] surgery where studies have shown no benefits in visualisation, bowel handling or complication rates between patients treated with bowel preparation and those given no bowel preparation. As a result of this inconclusive evidence, several studies have established that practice varies significantly between countries, and even surgeons in the same institution[ 17 , 18 ].…”
Section: Introductionsupporting
confidence: 82%
“…In recent years, more and more studies have found that MBP has no proven benefits and should be omitted in most colorectal and urologic surgeries (1,(17)(18)(19)(20)(21). However, studies specifically related to gynecologic patients are scant.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it might induce electrolyte disturbances, dehydration, insomnia, general weakness on the day of surgery, and gastrointestinal discomfort postoperatively. 5,6 Although systemic reviews could not demonstrate any significant benefit of MBP regarding intraoperative and perioperative complications, [7][8][9][10] MBP is still performed in many institutes before various transabdominal surgeries. [11][12][13] The anterior approach to the lumbar spine can allow direct and wide exposure of the anterior column, which has many advantages in spinal reconstruction surgery.…”
Section: Introductionmentioning
confidence: 99%